FAKTOR DETERMINAN SOSIAL DAN GAMBARAN KEJADIAN POST TRAUMATIC SYNDROME DISORDER (PTSD) PASCA BANJIR DI DKI JAKARTA DAN BEKASI TAHUN 2020 - THRESYA FEBRIANTI; Nurfadhillah Nurfadhillah; Mitha Nurhjanah; Tiara Kautsa Aliefya (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
Floods in the Greater Jakarta Area in February 2020 resulted in many losses such as casualties and damage to infrastructure. The psychological impact that often occurs after a disaster is Post Traumatic Stress Disorder (PTSD), if this problem is not addressed, it will have an impact on public health in the future. This study aims to look at the prevalence of Post-Flood PTSD and to analyze the Social Determinants of the Risk of Post-Flood PTSD. This research is able to answer the challenges in taking preventive measures for PTSD after the flood disaster. This research is an analytical study with a cross sectional study approach with a total sample of 100 people and selected by purposive sampling. The results will be analyzed bivariately. More than half the age of the respondents are in the adolescent age group (12-25 years) (65%), are female (69%), half of the respondents work 51%, more than half of the respondents received low family support (51%), received low peer support (50%), did not receive volunteer support ( 66%), did not receive the support of religious leaders (53%). There is no relationship between respondent characteristics, family support, friends, relative volunteers and religious leaders.